Spatio-temporal variations and input patterns on the legacy and novel brominated flame retardants (BFRs) in coastal rivers of North China - Liu, Lin; Zhen, Xiaomei; Wang, Xinming; Zhang, Daochang; Sun, Linting; Tang, Jianhui (Environmental pollution (1987), 2021)
Decabromodiphenyl ether (BDE209) has been subject to restrictions since 2018 in developed countries but is still manufacturing in China. Decabromodiphenyl ethane (DBDPE) is widely used as a replacement for BDE209. To better understand the behaviors and fates of these legacy and novel brominated flame retardants (BFRs), water samples were collected from the estuaries of 36 rivers that drain into the Bohai Sea (BS) and North Yellow Sea (NYS) in 2017 and 2018. The results showed that BDE209 was still the predominant compound with a median concentration of 2470 pg L−1, whereas DBDPE had a median concentration of 129 pg L−1. Spatially, relatively high concentrations were observed in the rivers near Laizhou Bay (LB), which is the manufacturing hub of BFRs. BDE209 concentrations were significantly higher in dry season than in wet season, which indicates a dominant process of dilution by precipitation during the wet season. DBDPE concentration showed no significant seasonal difference. This implies that wet deposition was the major additional source of DBDPE during the wet season, and the concentration increased further during the autumn as a result of a time-lag effect. The BFR concentrations in urban rivers were lower than those reported by a study undertaken in August 2013. An increase in the BFR concentrations in rural rivers since 2013 suggested increases in the use and non-point source emissions of BFRs in some remote aquatic environments. The estimated annual inputs of BDE209 and DBDPE into the BS were ∼95.9 kg yr−1 and ∼26.8 kg yr−1, respectively, whereas those into the NYS were ∼24.1 kg yr−1 and ∼8.38 kg yr−1. The results revealed an ecological risk of BDE209 in winter especially in the Xiaoqing River, thus suggesting the impact of BDE209 on the aquatic environment and human health. [Display omitted] •BDE 209 was the predominant compounds in rivers around the Bohai Sea.•Extremely higher levels of BDE 209 were found in dry season than in wet season.•Wet deposition is an important additional source of DBDPE in rivers.•BFRs increased in rural rivers but decreased in urban rivers within recent five years.•BDE209 may has reached a quasi-steady state but DBDPE showed an unsteady discharge. Capsule: Contrast to DBDPE, BDE209 is the predominant BFRs in rivers and shows distinct seasonal variation due to the dilution effect of rainwater in wet season.